2013
DOI: 10.1186/1471-2407-13-187
|View full text |Cite
|
Sign up to set email alerts
|

TP53p.R337H is a conditional cancer-predisposing mutation: further evidence from a homozygous patient

Abstract: BackgroundAdrenocortical carcinomas (ACCs) are among the most common childhood cancers occurring in infants affected with the Li-Fraumeni and Li- Fraumeni-like (LFS/LFL) syndromes, which are caused by dominant germline mutations in the TP53 gene. In Brazil, a particular mutation, occurring in the tetramerisation domain of the gene, p.R337H, is exceedingly common due to a founder effect and is strongly associated with ACC. In this report, we describe the phenotype and long-term clinical follow-up of a female ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
(38 reference statements)
0
12
0
1
Order By: Relevance
“…Therefore, once tuned to mutant phenotype in a pH-dependent manner, this protein may interfere with p53 oligomerization in a way that may prevent the assembly of wild-type p53 complexes, thus making it unnecessary to eliminate the wild-type allele through LOH. This hypothesis may also account for the observation that tumor patterns in subjects who have inherited two mutant alleles are not more severe than in heterozygote carriers [31]. While the exact disease-causing mechanism of the p.R337H mutation remains elusive, alternative hypotheses should be considered, such as the influence of environmental changes onto pH and occurrence of constant, more subtle changes to oligomerisation in vivo without the requirement for drastic pH changes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, once tuned to mutant phenotype in a pH-dependent manner, this protein may interfere with p53 oligomerization in a way that may prevent the assembly of wild-type p53 complexes, thus making it unnecessary to eliminate the wild-type allele through LOH. This hypothesis may also account for the observation that tumor patterns in subjects who have inherited two mutant alleles are not more severe than in heterozygote carriers [31]. While the exact disease-causing mechanism of the p.R337H mutation remains elusive, alternative hypotheses should be considered, such as the influence of environmental changes onto pH and occurrence of constant, more subtle changes to oligomerisation in vivo without the requirement for drastic pH changes.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] TP53 mutations have been reported in ACC at frequencies ranging from 10% to 70% and have been associated with decreased disease-free survival and poor outcomes. [23][24][25][26] Germline TP53 mutations have also been linked with the development of ACC, particularly in paediatric patients with a family history of LFS and Li-Fraumeni-like Syndrome. 26 In this study, the mean age of the patients with ACC with and without TP53 mutation was 59.4 years versus 50.2 years, respectively, and no TP53-mutated ACC was identified in a patient younger than 46 years.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Germline TP53 mutations have also been linked with the development of ACC, particularly in paediatric patients with a family history of LFS and Li-Fraumeni-like Syndrome. 26 In this study, the mean age of the patients with ACC with and without TP53 mutation was 59.4 years versus 50.2 years, respectively, and no TP53-mutated ACC was identified in a patient younger than 46 years. Patient-matched normal specimens required to definitively determine the germline status of TP53 mutation were not available for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Pomimo wcześniejszych alternatywnych teorii, ostatnie badania potwierdzają, że wysoki współczyn-nik występowania tej mutacji u około 0,3% populacji tego regionu wynika z wystąpienia efektu założyciela w populacji Brazylii. W południowej Brazylii częstość występowania ACC u dzieci jest 10-15-krotnie wyższa niż w innych częściach świata i jest silnie związana z mutacją p.R337H [115][116][117].…”
Section: Prace Poglądoweunclassified
“…Despite the previous alternative theories, a recent study has confirmed that the high prevalence of this mutation, around 0.3% in the population of this region, results from the occurrence of a founder effect in the Brazilian population. In Southern Brazil the incidence of childhood ACC is 10-15 higher compared with other parts of the world, being strongly associated with the p.R337H mutation [115][116][117].…”
Section: Prace Poglądowementioning
confidence: 99%